Reimagining transitional justice through participatory art - Shefik, Sherin (International journal of transitional justice, 2018)
‘Participatory art’ is a genre of art that focuses on the participation of people as the central artistic medium and material, as opposed to production by a single artist, and on the artistic process, as opposed to a definite final product. It is argued that transitional justice, reimagined through the conceptual lens of participatory art, would focus more on participation, on localism, on empowering and mobilizing at grassroots level, and on exploration of creative and uncensored processes, rather than focusing solely on preconceived state-centric models that dictate or control outcomes. It is further argued that the practical manifestation of participatory art is overlooked as an effective transitional justice tool. Using specific examples, the article explores how participatory art is a context-specific, collaborative and bottom-up process that can contribute to individualized and collective healing, make the invisible visible, extend social responsibility, restore collective memory, repair the social fabric, reclaim truths and foster collective change.